Two-dimensional materials in biomedical, biosensing and sensing applications. (18th November 2020) - Rohaizad, Nasuha; Mayorga-Martinez, Carmen C.; Fojtů, Michaela; Latiff, Naziah M.; Pumera, Martin
Abstract : 2D materials are at the forefront of materials research, advancing in applications for biomedical and bio/sensing. We elucidate properties of 2D materials beyond graphene that are relevant to those applications, as well as their correlation with toxicity. Abstract : Two-dimensional (2D) materials are at the forefront of materials research. Here we overview their applications beyond graphene, such as transition metal dichalcogenides, monoelemental Xenes (including phosphorene and bismuthene), carbon nitrides, boron nitrides along with transition metal carbides and nitrides (MXenes). We discuss their usage in various biomedical and environmental monitoring applications, from biosensors to therapeutic treatment agents, their toxicity and their utility in chemical sensing. We highlight how a specific chemical, physical and optical property of 2D materials can influence the performance of bio/sensing, improve drug delivery and photo/thermal therapy as well as affect their toxicity. Such properties are determined by crystal phases electrical conductivity, degree of exfoliation, surface functionalization, strong photoluminescence, strong optical absorption in the near-infrared range and high photothermal conversion efficiency. This review conveys the great future of all the families of 2D materials, especially with the expanding 2D materials' landscape as new materials emerge such as germanene and silicene.